Legal Protection for Consumers of Cosmetic Products Through Consumer Education - Duhita Driyah Suprapti; Salman Alfarisi; Shofriya Qonitatin Abidah; Anis Widyawati; Panggih Kusuma Ningrum (Jurnal Pengabdian Hukum Indonesia (Indonesian Journal of Legal Community Engagement) JPHI, 2026)
In today’s world, beauty and self-care have become essential aspects of daily life, making cosmetic products an integral part of modern society. Beyond enhancing appearance and self-confidence, cosmetics have become a medium for personal expression. However, consumer purchasing decisions are often influenced by social media, market trends, and sustainability values, while awareness of consumer rights and product safety remains relatively limited. One important aspect of cosmetic safety is the Period After Opening/PAO indicator, which specifies the period during which a cosmetic product remains safe to use after it has been opened. This community service activity aimed to improve public understanding of the importance of PAO information and promote greater awareness of consumer rights and safe cosmetic use. The program was implemented using an empirical legal approach supported by qualitative methods, including educational activities, surveys, and interviews to identify participants’ perceptions and levels of understanding regarding PAO information. The results revealed significant disparities in PAO literacy between individuals with higher educational backgrounds and those with lower levels of formal education, indicating unequal access to essential information related to cosmetic safety. The activity demonstrated that educational interventions can enhance public awareness of PAO indicators and encourage more informed and responsible consumer behavior. These findings emphasize the importance of strengthening public education initiatives and regulatory oversight to ensure consumer protection and promote the safe use of cosmetic products. This community service contributes to the achievement of the Sustainable Development Goals/SDGs, particularly SDG 3 (Good Health and Well-being) through the promotion of safer cosmetic practices, SDG 4 (Quality Education) by improving public literacy on cosmetic safety and consumer rights, and SDG 12 (Responsible Consumption and Production) by encouraging informed purchasing decisions and responsible consumption of cosmetic products.